Effects of grain processing and lipid addition to finishing diets on cattle performance and blood constituents - LaBrune, H.J.; Trater, A.M.; Pike, J.N.; Montgomery, Sean P.; Farran, T.B.; Sindt, J.J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Experiments were conducted to evaluate effects of grain processing and lipid source on finishing cattle performance, carcass characteristics, and plasma concentrations of glucose, urea, and α-amino nitrogen (amino acids). Eighty yearling Hereford x Angus steers (847 lb) were fed diets containing either steam-flaked corn or dry-rolled corn, both fed with and without 4% added tallow. In a fifth diet, ground flaxseed (equivalent to 4% lipids) replaced a portion of steam-flaked corn. Diets were fed once daily for 85 days. As expected, cattle fed steam-flaked corn were more efficient than steers fed dry-rolled corn. Adding tallow had little effect on performance. Including flaxseed resulted in performance similar to that with tallow addition. Plasma glucose concentrations measured 2 hours after feeding were higher for steers fed steam-flaked corn than for steers fed dry-rolled corn, and were higher for cattle fed tallow than for those fed no supplemental fat. Steers fed the flax/steam-flaked corn combination had lower plasma glucose concentrations 2 hours after feeding than those fed steam flaked corn with added tallow (P<0.05). Steam flaking corn increased performance and elevated glucose concentrations compared to dry rolling, suggesting that increasing the ruminal degradable starch allowed for a greater supply of substrates for gluconeogenesis. Adding flaxseed resulted in lower levels of plasma glucose after feeding, compared to tallow.
Keywords: Beef; Steam-flaked corn; Dry-rolled corn; Flax; Tallow